PENGARUH PENGETAHUAN PERPAJAKAN, NASIONALISME, DAN KEPERCAYAAN PADA PEMERINTAH TERHADAP KEPATUHAN WPOP - Setiady, Mila Aprilia; Budyastuti, Triyani (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
This research aims to analyze the influence of Tax Knowledge, Nationalism, and Trust in the Government on Individual Taxpayer Compliance registered at KPP Pratama Kalideres. This research employs a quantitative approach using the Partial Least Square - Structural Equation Modeling (PLS-SEM) technique through SmartPLS 4.0 software. The sample consists of 100 respondents selected using purposive sampling. The results indicate that tax knowledge and nationalism have a positive and significant effect on taxpayer compliance, whereas trust in the government does not show a significant effect. These findings suggest that knowledge and nationalist attitudes are more dominant factors than institutional trust in influencing tax compliance behavior.